A Protocol for the Effective Utilization of Energy in Wireless Sensor Network - Anand, Santosh; Radhakrishna, Pillai Atulya (International Journal of Engineering and Technology, 2018)
In current technology Adhoc network is most commonly used in communication network. Major parts of the Adhoc network devices are based on the sensor nodes. Sensor devices operated on the battery so energy is vital constraint. Effective Utilization of the energy of the sensor nodes and sensor networks to the full extent is highly impracticable. Optimization of the network root and the load balancing in coverage helps to maximize the lifetime of the sensor network considerably. The research carry out on sensor network, deployment model is proposed which essentially finds the optimized roots with the help ofÂ neighbour discovery algorithm which find the neighbour and non neighbour nodes and analysis the load of the network based on Packet Retrieval in RREQ, throughput, average energy consumption, packet delivery ratio and packet drop.Â